Quantitative proteome changes in Arabidopsis thaliana suspension-cultured cells in response to plant natriuretic peptides - Ilona Turek; Janet I. Wheeler; Chris Gehring; Helen R. Irving; Claudius Marondedze (Data in Brief, 2015)
Proteome changes in the Arabidopsis thaliana suspension cells in response to the A. thaliana plant natriuretic peptide (PNP), AtPNP-A (At2g18660) were assessed using quantitative proteomics employing tandem mass tag (TMT) labeling and tandem mass spectrometry (LC–MS/MS). In this study, we characterized temporal responses of suspension-cultured cells to 1 nM and 10 pM AtPNP-A at 0, 10 and 30 min post-treatment. Both concentrations we found to yield a distinct differential proteome signature. The data shown in this article are associated with the article “Plant natriuretic peptides induce a specific set of proteins diagnostic for an adaptive response to abiotic stress” by Turek et al. (Front. Plant Sci. 5 (2014) 661) and have been deposited to the ProteomeXchange with identifier PXD001386.